Approval of the Access Rules and Charging Methodology proposed by BBLC Company (“BBLC”, “Licensee”) including : direction of approval pursuant to Standard Licence Conditions 10 and 11A of the gas interconnector Licence.: direction of approval pursuant to Standard Licence Conditions 10 and 11A of the gas interconnector Licence. (2021) - Unknown
No abstract available